2016
DOI: 10.1177/0194599816634627
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Volume and Thyroidectomy Outcomes

Abstract: This meta-analysis showed that patients who received thyroidectomies performed by high-volume hospitals and surgeons had shorter LOS and lower costs compared with those treated by low-volume hospitals and surgeons. In addition, in-hospital survival rates were better in patients treated by high-volume surgeons. Further research is needed to define the learning curve for thyroidectomy and to clarify how hospital volume and surgeon volume affect its success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 43 publications
0
35
1
Order By: Relevance
“…In contrast, a recent study showed that although larger surgeon volumes were associated with lower rates of vocal cord palsy and hypoparathyroidism, the absolute effect of volume on outcomes was modest, especially in hospitals with low complication rates [ 9 ]. Although the evidence for a volume-outcome relationship in thyroidectomy appears strong, other confounding surgeon and hospital-specific factors may also play an important role [ 10 ]. Nevertheless, the American Thyroid Association and the American Association of Endocrine Surgeons both recommend that thyroidectomy should be performed by high-volume surgeons where possible, defined as a minimum of 20 thyroidectomies annually [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a recent study showed that although larger surgeon volumes were associated with lower rates of vocal cord palsy and hypoparathyroidism, the absolute effect of volume on outcomes was modest, especially in hospitals with low complication rates [ 9 ]. Although the evidence for a volume-outcome relationship in thyroidectomy appears strong, other confounding surgeon and hospital-specific factors may also play an important role [ 10 ]. Nevertheless, the American Thyroid Association and the American Association of Endocrine Surgeons both recommend that thyroidectomy should be performed by high-volume surgeons where possible, defined as a minimum of 20 thyroidectomies annually [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, different volume groups had similar in-hospital mortality rates. Unfortunately, morbidity was out of the scope of this study [ 12 ] (ELIII, RGC).…”
Section: Resultsmentioning
confidence: 99%
“…All studies agree that operations performed by experienced surgeons and in high volume centers (> 100 thyroidectomies / year) show a lower complication rate and a shorter hospital stay. (8) In particular, it has been shown that the length of stay and complications are more determined by the surgeon experience than by hospital volume, which does not have a consistent association with the results. 3Some study described also a threshold (> 25 total thyroidectomies/y) that identify a high-volume thyroid surgeon and it is associated with improved patient outcomes.…”
Section: Discussionmentioning
confidence: 89%